ANALISIS KEUANGAN DANA TALANGAN UMROH PADA PT. FIRNANDO TEAM INDONESIA CABANG BENGKULU - Herlina; Muhamad Nasir (Universitas Prof.Hazairin,SH Bengkulu, 2025)
The purpose of this research to analyze the financial mechanism of sharia-based Umrah bailout financing for Umrah pilgrims at PT. Firnando Team Indonesia Bengkulu Branch. The research method uses descriptive approach. The results show that the Umrah bailout financing at PT. Firnando Team Indonesia Bengkulu Branch emphasizes the principles of justice and transparency without elements of usury. This program makes the pilgrims very easy to carry out Umrah with flexible payments, but still requires commitment in repayment according to the agreement. The research concludes that the Umrah bailout financing funds at PT. Firnando Team Indonesia Bengkulu Branch is in line with the principles of Islamic financing and has a positive impact on increasing the accessibility of Umrah worship for the community.